How Prepared Are US States for a Recession: An Update - Elder, Erick M. (Journal of Applied Business and Economics, 2024)
Rainy day funds are a common tool that most US states use to help mitigate the fiscal stress caused by economic slowdowns that reduce state government revenue. Except for a very brief (but very severe) recession in 2020 caused by the pandemic, most states have generally experienced an economic expansion since the end of the Great Recession in 2009 giving them well over a decade to accumulate savings in a Rainy-Day Fund (RDF) to help weather an economic downturn. This paper examines how state RDF’s have changed over the past decade and how these changes have affected each state’s ability to weather an economic downturn.